THE MIGRATION SITUATION AND MIGRATION POLICY IN KALMYKIA - VOLGIN, Vladimir (CENTRAL ASIA AND THE CAUCASUS, 2004)
According to the results of the nationwide population census carried out in October 2002, there are 292,400 people living in the Republic of Kalmykia. Information on the population’s ethnic composition has still not been published, but, according to similar data for 1989, Kalmyks accounted for 45.4%, Russians for 37.7%, Darghins for 4%, Chechens for 2.6%, and so on.1 Compared with the last census, the size of the population had shrunk by 30,000 people (9.3%), and the republic was the only territory in the Northern Caucasus and the Russian South where a decrease in the number of residents was recorded.2 We will note that there is a continuous natural increment (the number of births exceeds the number of deaths) in the population in Kalmykia. But this is not enough to compensate for the migration decrement (more people are leaving than arriving), which led to the drop in its population. For example, in 2001, the natural increment amounted to 173 people, in 2000 to 92, and in 2003 to 464, with a migration decrement of 2,182, 1,237, and 1,692 people, respectively.3